The Thai students in the University of the Philippines in the school year 1972-1973 their study habits and attitudes - Vanasinthu, Patcharaporn 1937- (s.n.], 1972)
This paper is a descriptive profile of the study habits and attitudes of Thai students enrolled at the University of the Philippines for the school year 1972-1973. The study provided some recommendations which will more or less redound to the benefit of the Thai students themselves, in terms of suggestions on how they could be helped in their study problems and difficulties.